MCPH1 deletion in a newborn with severe microcephaly and premature chromosome condensation - Pfau, Ruthann B.; Thrush, Devon Lamb; Hamelberg, Elizabeth; Bartholomew, Dennis; Botes, Shaun; Pastore, Matthew; Tan, Christopher; del Gaudio, Daniela; Gastier-Foster, Julie M.; Astbury, Caroline (European journal of medical genetics, 2013)
A newborn with severe microcephaly and a history of parental consanguinity was referred for cytogenetic analysis and subsequently for genetic evaluation. While a 46,XY karyotype was eventually obtained, premature chromosome condensation was observed. A head MRI confirmed primary microcephaly. This combination of features focused clinical interest on the MCPH1 gene and directed genetic testing by sequence analysis and duplication/deletion studies disclosed a homozygous deletion of exons 1–11 of the MCPH1 gene. This case illustrates a strength of standard cytogenetic evaluation in directing molecular testing to a single target gene in this disorder, allowing much more rapid diagnosis at a substantial cost savings for this family.